Tindak Pidana Kerusakan Lingkungan Akibat Pertambangan Minyak Dan Gas Bumi - Bina Eradany (Journal on Education, 2020)
The research title of this thesis is the crime of environmental damage due to oil and gas mining. As for the objectives of the research, namely to find out the procedure for determining DPO suspects in the investigation of criminal conspiracy to commit narcotics precursor crimes, to find out the obstacles investigators from the Medan Police Narcotics Research Unit in investigating criminal conspiracy to commit narcotics precursor crimes and to find out the efforts of investigators from the Narcotics Research Unit of the Polresta Police Medan is currently investigating criminal conspiracy to commit narcotic precursor crimes. The results of this study indicate that criminal provisions for environmental damage resulting from mining are regulated through Government Regulation Number 27 of 2012, Law Number 4 of 2009, Law Number 23 of 1997 and Law Number 23 of 1997. Law Number 4 of 1982. Factors that cause environmental damage as a result of oil and gas mining include accidents, contamination of polluting waste, use of tools and materials that are not in accordance with standards and the presence of sludge produced. Efforts made to minimize companies conducting business activities without causing environmental damage in community areas include reforming policy regulations, being careful in making policies, establishing high environmental management standards, making mining policies with an emphasis on community aspects and providing optimal protection for the community.